Effect of Tool Plunge Depth and Pin Profile on Mechanical Properties of Friction Stir Spot Welded AA5052 Joints / Nurul Muhayat...[et al.] - Muhayat, Nurul; Triyono, Rizky Danu Rahmanto; Zubaydi, Achmad (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
Friction stir spot welding (FSSW) is a new developed solid state joining technology. Automotive industry introduces FSSW to substitute resistance spot welding process to join Aluminum alloy. In this study, FSSW is applied to join 5052-H32 aluminum alloy sheets. The AA5052-H32 sheets with the thickness of 2 mm was welded using friction stir spot welding. The influence of tool plunge depth and pin profile on macrostructure, microstructure, and mechanical properties of the joints were experimentally investigated. Three different tool pin profile of cylinder, truncated cone, square pin and four different tool plunge depth of 2.2, 2.4, 2.6, 2.8 mm were used to fabricate the joint. The result shows that the increase of tool plunge depth resulted in the increase of frictional heat that affected to the wider area of stir zone and the coarser grain size. It resulted in the increase of tensile shear load of the joint. The maximum tensile shear load obtained at tool plunge depth of 2.6 mm for all variation tool pin profile. The further increase of tool plunge depth of 2.8 mm produced the lower joint strength than previous tool plunge depth. The tool pin profile affected to the physical and mechanical properties of the friction stir spot welded of AA5052 joint. Truncated conical pin resulted in the narrower of stir zone, whereas square pin resulted in the wider of stir N. Muhayat, Triyono, R. D. Rachmanto, A. Zubaydi zone. The best tensile shear load obtained in the square pin profile of 4.07 kN.